HUBUNGAN PERAN KELUARGA DENGAN TINGKAT KEKAMBUHAN PASIEN GANGGUAN JIWA DI PUSKESMAS PESANGGRAHAN KECAMATAN KUTOREJO MOJOKERTO - Hamidah Fajrin Rusydy; Henry Sudiyanto; Atikah Fatmawati (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
The recurrence rate of people with mental disorders in Indonesia annually increases to 50% -92% of the population. The purpose of this study was to analyze the role of families with the degree of recurrence of people with mental disorders in Pesanggrahan Health Center, Kutorejo Mojokerto. This research uses quantitative analytic descriptive design through a retrospective cohort approach using non-probability sampling techniques with purposive sampling. The study was conducted in March-April 2019. Measuring instruments using a questionnaire with the Spearman rank statistical test. The results showed that almost all families of mental patients have a role in the care of patients as much as 93.3% with a frequency recurrence rate rarely of 80%. Based on the calculation of statistical specs, with a significant value α = 0.05 obtained r = 0.014 which means it is smaller than the value of the significant level (0.014 <0.05) then H1 is accepted, there is a significant relationship between the roles of families and patients who relapse. mental disability. The role of the family is very important for the level of recurrence of mental patients. It is recommended to pay more attention to families with mental disorders